2013
DOI: 10.1287/serv.2013.0047
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Economic Analysis of the Cloud Brokering Platform Under Uncertainty: Choosing a Risk/Profit Trade-off

Abstract: This paper develops models for the analysis of a cloud brokering platform under conditions of risk and demand uncertainty, focusing on controlling the risk of not delivering the quality of service required by users. Such risk can occur as a result of inherent limitations of the best-effort connectivity. We take the approach of modern portfolio theory and show how the trade-off between risk and profit can be chosen by selecting efficient connectivity portfolios that combine the best-effort connectivity of diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…Нехай  − випадкова подія з множини  можливих майбутніх станів, яка стається з деякою ймовірністю   . Тоді замість цільової функції (11) максимізується очікувана (expected) поточна вартість…”
Section: )unclassified
“…Нехай  − випадкова подія з множини  можливих майбутніх станів, яка стається з деякою ймовірністю   . Тоді замість цільової функції (11) максимізується очікувана (expected) поточна вартість…”
Section: )unclassified
“…Therefore, the selection of the broker–carrier scenario does not limit the subsequent analysis. Nevertheless, we have analysed the case of pure broker with OptiCloud and have found that it is inferior to combined broker/carrier for high quality service .…”
Section: Qualitative Description Of Cloud Computing Businessmentioning
confidence: 99%
“…Markowitz has pioneered modern financial portfolio theory, and in the recent years, financial portfolio optimization has developed into a rich body of models and applications . In the context of modern communication and information services, the portfolio theory approach and business optimization has been used by Gaivoronski and Zoric, Nesse et al, and Gaivoronski et al…”
Section: Introductionmentioning
confidence: 99%
“…Markowitz 10 has pioneered modern financial portfolio theory, and in the recent years, financial portfolio optimization has developed into a rich body of models and applications. 11,12 In the context of modern communication and information services, the portfolio theory approach and business optimization has been used by Gaivoronski and Zoric, 13 Nesse et al, 14 and Gaivoronski et al 15 The development of the model described below is the outcome of a research process with case study characteristics. 16 In order to understand the cloud service providers' role in the value chain, to identify relevant cost and income objects and their hierarchy, to elaborate the model structure, and to finally assign relevant financial data, we conducted several semistructured interviews with key persons both at the telecommunication holding company and the affiliated cloud service provider.…”
Section: Introductionmentioning
confidence: 99%